Variable structure controller and observer applied to induction machine - Gomes da Silva, Sandro [UNESP]; Fernandes Garcia, Jose Paulo [UNESP]; Minhoto Teixeira, Marcelo C. [UNESP] (My University, 1998)
This work will propose the control of an induction machine in field coordinates with imposed stator current based on theory of variable structure control and sliding mode. We describe the model of an induction machine in field coordinates with imposed stator current and we show the design of variable structure control and sliding mode to get a desirable dynamic performance of that plant. To estimate the inaccessible states we will use a state observer (estimator) based on field coordinates induction machine. We will present the results of simulations in any operation condition (start, speed reversal and load) and with parameters variation of the machine compared to a PI control scheme.